Hubungan Motivasi Belajar Dengan Prestasi Akademik Siswa Pada Mata Pelajaran Biologi di Kelas X SMA Negeri Insana Tengah Maubesi - Nahak, Febiana Y; Kristanti, E; Oetpah, Finsensius (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
Research with the title Relationship of Student Motivation and Academic Achievement in Biology Subjects in Class X Middle Insana Middle School, Maubesi aims to find out the magnitude of student motivation in biology, to determine the level of student academic achievement and see how much the role of motivation on academic achievement the student. The data analysis technique used in this research is Product Moment Correlation. The results showed that the average student motivation in Biology in Class X Middle Insan Maubesi SMAN was 144.82 with the highest value of 185 and the lowest value obtained was 97, included in the HIGH category, while the average academic achievement of students in Biology class X in Middle Maubesi Middle School of 80.72 with the highest score of 92 and the lowest value of 75, included in the very high category. The results of the Produck Moment analysis show that there is no significant relationship between motivation and academic achievement of students in Biology class X at SMAN Insana Tengah Maubesi with a correlation coefficient of 0.053 included in the very low category.